Analysing the resilience of military supply network and simulation against disruptions. (2016) - Zhou, Qingzhong; Xiong, Biao; Li, Bixin; Huang, Jin; Lu, Sixi
In this paper, we study the effectiveness of military supply systems in complex and uncertain environment from the perspective of complex network topologies. Our goal is to provide insights on how to explore military supply networks and analyse the networks' resilience against different disruptions. We first propose an analysis process of the resilience for military supply networks. Then, we present two military supply growth models - key units priority (KUP) growth model and cost minimisation priority (CMP) growth model based on real military supply activities, which can be used to generate two military supply networks. We also present a new taxonomy of resilience metrics for military supply networks. Through computer simulation, we find that KUP supply network has poorer resilience against targeted disruptions but higher supply efficiency compared with other networks. While the connectivity of demand nodes in CMP supply network has better adaptability, it is of lower supply efficiency against both random and targeted disruptions. Through analysis, we can provide decision-makers with references when they choose supply patterns and deploy logistics defence forces.